Ethical Considerations Regarding Psychedelics for Clinical Pain Research - Robinson CL; Slitzky M; Schatman ME; Yong RJ; Lehman AD; Kaynar AM; Shivanekar SP; Emerick T (Journal of Pain Research)
Christopher L Robinson,1,* Matthew Slitzky,2,* Michael E Schatman,3,4 R Jason Yong,1 April D Lehman,5 Ata Murat Kaynar,6 Sharvari P Shivanekar,7 Trent Emerick6 1Department of Anesthesiology, Perioperative & Pain Medicine, Harvard Medical School, Brigham & Women’s Hospital, Boston, MA, USA; 2Burke Rehabilitation, Montefiore Health System, White Plains, NY, USA; 3Department of Anesthesiology, Perioperative Care, and Pain Medicine, NYU Grossman School of Medicine, New York, NY, USA; 4Department of Population Health-Division of Medical Ethics, NYU Grossman School of Medicine, New York, NY, USA; 5Office of Research Protections, University of Pittsburgh Medical Center, Pittsburgh, PA, USA; 6Department of Anesthesiology and Perioperative Medicine, Chronic Pain Division, University of Pittsburgh Medical Center, Pittsburgh, PA, USA; 7Department of Consultation-Liaison Psychiatry, University of Pittsburgh Medical Center, Pittsburgh, PA, USA*These authors contributed equally to this workCorrespondence: Trent Emerick, University of Pittsburgh Medical Center, 5750 Centre Ave #400, Pittsburgh, PA, 15206, USA, Email emericktd@upmc.eduAbstract: Psychedelics, substances with a long history of cultural and medicinal use, are experiencing a resurgence in clinical research, particularly in psychiatry. Despite their classification as Schedule I drugs, recent studies suggest therapeutic potential, particularly in treating refractory depression. With chronic pain representing a major health concern and with few non-opioid treatment options available, psychedelics are being explored as alternative treatment modalities. The National Institutes of Health (NIH) now funds psychedelic research, marking a shift from previous decades of limited funding. However, ethical considerations loom large. Vulnerable populations, such as those with chronic pain that impairs their autonomy, require careful consideration by researchers of risks and benefits. Additionally, researchers and interested entities must navigate complex regulatory landscapes involving the United States Food and Drug Administration (FDA) and Drug Enforcement Administration (DEA) when considering pursuing possible research. Furthermore, transparent collaboration among stakeholders—patients, researchers, and regulatory bodies—is crucial for participant safety and successful research. Although a number of ethical approaches can be taken, we posit that stakeholders consider utilizing principal-based research ethics, comprised of the principles of autonomy, beneficence, justice, and nonmaleficence, to guide the process. Ultimately, balancing therapeutic promise with ethical integrity is paramount. Careful planning, collaboration, and adherence to ethical principles can increase the likelihood that psychedelic research in chronic pain management progresses responsibly, offering hope for patients while safeguarding their well-being.Keywords: ethics, psychedelics, chronic pain, research, drug enforcement administration